Letters from the pandemic: Nursing student narratives of change, challenges and thriving at the outset of COVID‐19. (19th April 2021) - Heilferty, Catherine McGeehin; Phillips, Lorraine J.; Mathios, Rebecca
Abstract: Aim: The aim of this study is to explore the experience of third year baccalaureate nursing students during the outbreak of the COVID‐19 pandemic. Design: Research design is a narrative analysis of archived letters written by nursing students in Spring 2020. Methods: Letters and other media were written between 1 April and 20 May 2020. Fifty‐six letters, some with accompanying audio or visual media, were submitted in late May 2020. Approval from the University Institutional Review Board was obtained to explore the letters through narrative analysis (Riessman, 2008). As the letters were considered archival, consent from the students for the analysis was not indicated. Once thematic categories were identified independently, the authors discussed the findings until a list of narrative categories and narrative exemplars were agreed on. Results: Three main thematic categories were found: stories of change, challenges and thriving. Conclusion: Findings were consistent with prior research and reveal new opportunities for understanding the perspectives and needs of undergraduate nursing students during times of crisis. Action by administrators and faculty are recommended.